Multiple Intelligence-based Activities: Its Effects on Essay Writing Skills - Agrissto Bintang Aji Pradana; Tri Pujiani; Meiliana Nurfitriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Writing an English essay requires complex abilities, such as critical thinking and academic writing. Nevertheless, it seems to be an obstacle to developing essay writing skills. Besides they are using a foreign language, the learning activities did not accommodate their personal traits and learning styles. This study aims to find out the profile of PGSD students’ Multiple Intelligence (MI) and the effect of MI-based learning activities on their essay-writing skills. This experimental research was conducted at Universitas Muhammadiyah Magelang in 2020. Furthermore, 60 out of 160 fourth-semester students at the Elementary School Teacher Education Department were involved as the sample. The primary data were obtained through tests supported by observation and interviews. The data were distributed to be normal and homogenous. Based on the statistical data analysis of the Independent t-test, Sig. (2-tailed) was 0.900 > 0.05. The average scores of the Experimental Group post-test also indicate higher than the one of the control group post-test scores. It concludes that MI-based activities influenced students’ essay-writing skills. The results could be a beneficial reference in promoting students’ essay-writing skills in higher education.